THE INFLUENCE OF E-SERVICE QUALITY TOWARDS CUSTOMER SATISFACTION AND CUSTOMER LOYALTY ON GOPAY ELECTRONIC WALLET USERS - Alvin Tiko Harijanto; Winston Watson (Jurnal Inovasi Penelitian, 2021)
The purpose of this study was to investigate the influence of electronic service quality towards consumer satisfaction using GOPAY electronic wallet on a daily transactions. In this study, the independent variables were application design, reliability, security/privacy, and customer service, while the dependent variables were customer satisfaction, and customer loyalty. The populations were customers who had used GOPAY electronic wallets for transactions. The total of collected respondents was 204 respondents and the researchers had successfully analysed 152 respondents as a sample. The data was collected through survey methods and questionnaires. The data then analysed by using SEM analysis model with Smart PLS 3. The results prove that the quality of electronic services have a significant influence on customer satisfaction. This study also finds that customer satisfaction has a positive effect towards customer loyalty.